Taxionomia e morfologia de Pomacea lineata (Spix, 1827) (Mollusca, Gastropoda, Ampullariidae) - Thiengo, Silvana Aparecida Rogel Carvalho (1987)
This work deals with the internal and external anatany of Pomacea lineata (SPIX, 1827). The descriptions and figures of the soft parts and shell, reproductive, digestive, excretory, respiratory, circulatory and nervous systems are given. Microanatomic studies of the male copulatory apparatus were made. The taxonomic problems related to the genus and the family names were pointed out. The shell and the radula are not available features to discriminate the species since the first showed instraspecific variation and the latter is very similar in all the family. Probably, in the male reproductive system are some of the diagnostic features of the species.